THE EFFECT OF WORK CULTURE ON THE SATISFACTION OF EMPLOYEES - Sarah Sabir Ahmad; Azfahanee Zakaria; Maznah Wan Omar (International Journal of Accounting, Finance and Business, 2018)
Organization culture is unique for each organization. This is because cultures are created by the managers or leaders to ensure smooth performance of the organization as better job satisfaction leads to overall well-being of the organization. Therefore, this paper aims to identify the relationship between the four (4) types of organizational culture based on the Competing Value Framework (Clan, Adhocracy, Market and Hierarchy) and job satisfaction among academics in universities in Malaysia. The research was carried out by using the 5point Likert Scale Measurement adapting the Organizational Culture Assessment Instrument (OCAI) that was utilized to measure data regarding Organizational Culture whereas to measure Job Satisfaction a five-item scale operational job satisfaction instrument was utilized. A sample of 100 academic staff was selected as the respondent by using simple random sampling. The goodness of measure of the data was analysed and subsequently Regression Analysis was conducted to determine the objectives of the study. The findings reveal that two variables namely Market and Clan culture have a positive and significant impact on job satisfaction with Market Culture being the most dominant culture impacting the job satisfactions among the academics in Malaysia. Optimistically, the findings will be able to shed some light in the marketing literature since it is projected that a dominant culture will influence on how an organization work, therefore identifying and strengthening this culture will bring the best from the employees from the organization.